2014
DOI: 10.1097/nmc.0000000000000069
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Triage

Abstract: Seven key triage categories from the literature were identified and best practices were developed for obstetric triage units from this systematic review. Both can be used to guide future practice and research within obstetric triage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 24 publications
0
11
0
2
Order By: Relevance
“…In a recent systematic review of literature on obstetric triage published from 1998 to 2013, the authors identified quality improvement strategies that track acuity, length of stay, and patient satisfaction as important components of best practice (Angelini & Howard, 2014). The obstetric triage unit functions uniquely as an outpatient assessment center in an inpatient unit in most hospitals.…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…In a recent systematic review of literature on obstetric triage published from 1998 to 2013, the authors identified quality improvement strategies that track acuity, length of stay, and patient satisfaction as important components of best practice (Angelini & Howard, 2014). The obstetric triage unit functions uniquely as an outpatient assessment center in an inpatient unit in most hospitals.…”
Section: Background and Significancementioning
confidence: 99%
“…T riage, in the context of health care, involves the process of determining the priority of patient care according to the urgency of their need for treatment and is often associated with emergency and disaster services (McBrien, 2009). Triage concepts have become part of obstetric practice to improve utilization of bed capacity, increase immediate and appropriate response to obstetric emergencies, decrease wait times, prevent unnecessary admissions, and standardize assessment (Angelini & Howard, 2014). Obstetric triage is defined as the ability to appropriately prioritize and assess pregnant women in a timely manner, to improve patient flow, and enhance patient safety (Paisley, Wallace, & DuRant, 2011).…”
mentioning
confidence: 99%
“…In many obstetric units in these hospitals, there is a separate triage area with dedicated staff to receive and rapidly assess women in order to quickly treat complications [8]. The Association of Women’s Health Obstetric and Neonatal Nurses (AWHONN) recommends that the triage assessment begin within 10 min of arrival to a facility [7].…”
Section: Introductionmentioning
confidence: 99%
“…A 2014 review of obstetric triage practices searched English language articles from 1998 to 2013 and of 33 relevant articles, none were from LMICs. 28 …”
Section: Reflectionmentioning
confidence: 99%